Cochrane the dauntless the life and adventures of Admiral Thomas Cochrane, 1775-1860 - Cordingly, David (Bloomsbury, 2007)
Thomas Cochrane was the epitome of the Romantic hero -- a man of action, whose bold and impulsive nature meant that he was often his own worst enemy. This impetuousness lay behind his early success, but also caused him to upset admirals and politicians and culminated in the 1814 Stock Exchange scandal, which saw him blackcalled by the British Establishment.